The sum of the digits is 9. If the tens digit is 'x', and the units digit is 9 - x.
The original number is ten times the tens digit plus the units digit, so the original number is 10x + 9 - x and that can be rearranged to 10x - x + 9, and simplified to 9x + 9.
When the number is reversed, the tens digit will now be ten time 9 - x plus the other digit 'x', which looks like this:
10(9 - x) + x which can be simplified to 90 - 9x + x which becomes 90 - 9x.
The second sentence in your problem says 'Original number minus the second number = 27'
So.... (9x + 9) - (90 - 9x) = 27 which simplifies to 9x + 9 - 90 + 9x = 27 which simplifies to 18x - 81 = 27, add 81 to each side, 18x = 108 and now divide by 18 to get x = 6.
Since x = 6 then 9 - x = 3
So the tens digit is 6 and units digit is 3. The 'number' is 63.
To check, 63 - 36 = 27
Hope this helps, Sabrina,